The effects of resistance training in osteoporosis: a systematic review - Andrade, Simone da Silva (2015)
Introduction: Currently the problems related to loss of bone mineral density (BMD) reach an average percentage of 7.9% to 16% of women aged equal or above 50 years, being regarded as a serious problem for public health. Aim: the study wasdoneto determine whether there is literature on controlled clinical trials of treatments in their resistance training and achieved positive outcomes in increasing BMD of volunteers. Methods: A review study based on recommendations PRISMA, which began with the selection of key terms through the DESC and MeSH. Soon after, held filters in major databases: SciELO; PUBMED and Google Scholar search site, for having many items that are not indexed in the above bases. We selected the key terms in the English language: Resistance Training, Strength Training, Osteoporosis, Calcium deficiency, Exercise, and the English language: Resistance Training, Strength Training, Osteoporosis, Calcium Deficiency, Exercise. The terms were entered in the search sites, separated by Boolean operators "AND" and "OR". The search and selection of the analyzed papers happened between May-June/2014. Results: After a systematic searcha total of06 clinical trials that met the eligibility criteria, and in only one of them there was no significant improvement in BMD were included. Conclusion: We found that the TR can be a positive proposal about their safety and effectiveness for people with problems related to BMD.